(3JQJjH CSeGA GdUMGHI GdPjf CNQL MOjKge GHf MfHd aj GdeSfOs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s ((3jhSa Hf Ydi GdTfGhi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi HJhMjOg hGdEYJQGa HQHhHjJg CcQefG CeG HYO , aEf MOjK GdeUWai Hg jYQa SHd GdESdGe acGf CcHQ GdcJH GdJi LeYJ ajg eeG hbY EdjfG hCYdGgG SfOkG Edi eUfag s
(3BNQgG (B:s
(3ef YfhGf (B: (3ef Qhi Yef de jS Yef de jSe bhdg (B: (3WdMI GHf eYQha Yf GeQCI ef YHO GdbjS Yf CNJ YHO Gddg Hf QhGMI bGd GdMGaX hgPG BNQ GdagQSI hQHeG LGA GdGSe ai ehVYjf JGQI eSei , hJGQI ecfi ceG CNQLg gh hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3eQJHI Ydi MQha GdeYLes
(3ddJbQjH Ydi WGdH GdeJfs
(3hGdQGZH ai Gdhbha Ydi GdSfOs
(3UhQJ Yf GdLGeY GdcHjQ UfYGA GdcJH GdeUGOQI s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs